Psychological changes and associated factors among patients with tuberculosis who received directly observed treatment short-course in metropolitan areas of Japan: quantitative and qualitative perspectives - Kae Nagahiro Shiratani (BMC, 2019)
Abstract Background The directly observed treatment short-course (DOTS) is one of the most effective tuberculosis (TB) control measures worldwide. However, despite its aim of providing comprehensive and humanistic care, few studies have examined its psychological effects from the patient's perspective. Thus, this study aimed to evaluate the psychological changes and identify associated factors among patients with TB undergoing the DOTS program in Japan. Methods This cross-sectional study recruited patients with TB receiving the DOTS program via 32 public health centers in four metropolitan cities in Japan. Surveys were administered to the patients and their attending public health or clinical nurses, who were responsible for their care and the DOTS program. Data were collected regarding the patients' demographic and clinical characteristics, post-traumatic growth (using the Post-Traumatic Growth Inventory-Short Form [PTGI-SF]), and medication adherence, alongside open-ended questions, from 2014 to 2015. Additionally, the patients' appraisal of the DOTS program's efficacy and nurses' assessment of the program's practices were measured using two original questionnaires. Factors associated with post-traumatic growth were analyzed using variable estimation, correlation analysis, and logistic regression. Thematic analysis was conducted on the open-ended responses. Results Questionnaires were returned by 127 patients (125 valid answers); 98 (78.4%) of the respondents were men. Their mean age was 63.3 (standard deviation: 15.8) years. The mean PTGI-SF score was 21.7 (standard deviation: 11.1). The logistic regression analysis found that post-traumatic growth was significantly associated with the patients' appraisal of the program's efficacy (odds ratio [OR] = 1.157, 95% confidence interval [CI] = 1.026-1.304) and nurses' assessment of the practices (OR = 1.307, 95% CI = 1.065-1.603). In the qualitative analysis, "Non-acceptance," "Frustration," and "Anxiety" were extracted as barriers to treatment; "Fear," "Acquiring a partner," "Relief," and "Belief" were extracted as treatment drivers; and "Life changes" and "Rebuilding oneself" were extracted as treatment outcomes. Conclusions The DOTS program in Japan improves patients' treatment adherence and leads to recovery and psychological growth. Even in other regions, it may be effective to incorporate this program's practices that place importance on partnerships with patients. It is also necessary to continue refined quantitative and qualitative evaluations.